1984
DOI: 10.1152/ajpregu.1984.247.5.r780
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of training-induced attenuation of postexercise ketosis

Abstract: We have examined the roles of liver glycogen and malonyl coenzyme A (CoA) in determining the degree of postexercise ketosis in endurance-trained and nontrained rats. Three groups of rats were run on a treadmill for 90 min: trained (2 h/day, 6 wk) and food restricted to 5.5 g/100 g body wt the night before the 90-min exercise bout (group 1), nontrained fed ad libitum (group 2), and nontrained food restricted (same as trained) (group 3). Liver glycogen was 34 +/- 5, 24 +/- 2, and 7 +/- 2 mg/g in groups 1, 2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Endurance-trained rats and humans have been reported to be more resistant to postexercise ketosis than untrained controls (Johnson, Walton, Krebs & Williamson, 1969;Johnson & Walton, 1971;Rennie, Jennett & Johnson, 1974;Winder, Hickson, Hagberg, Ehsani & McLane, 1979), though other studies (Grollman & Phillips, 1954;Passmore & Johnson, 1958;Johnson & Passmore, 1960;Askew, Dohm & Huston, 1975;Koeslag, Noakes & Sloan, 1980;Beattie & Winder, 1984) have shown that it is the athletes who develop the higher blood concentrations of ketone bodies during the recovery from a standard bout of exercise. The only factor which appears to distinguish these two groups of studies is diet.…”
Section: Introductionmentioning
confidence: 98%
“…Endurance-trained rats and humans have been reported to be more resistant to postexercise ketosis than untrained controls (Johnson, Walton, Krebs & Williamson, 1969;Johnson & Walton, 1971;Rennie, Jennett & Johnson, 1974;Winder, Hickson, Hagberg, Ehsani & McLane, 1979), though other studies (Grollman & Phillips, 1954;Passmore & Johnson, 1958;Johnson & Passmore, 1960;Askew, Dohm & Huston, 1975;Koeslag, Noakes & Sloan, 1980;Beattie & Winder, 1984) have shown that it is the athletes who develop the higher blood concentrations of ketone bodies during the recovery from a standard bout of exercise. The only factor which appears to distinguish these two groups of studies is diet.…”
Section: Introductionmentioning
confidence: 98%
“…, ; Askew et al . ; Beattie & Winder, ). This coincides with two‐ to threefold higher ex vivo rates of βHB and AcAc oxidation in gastrocnemius muscle homogenates presented with concentrations of both βHB and AcAc at 0.1 and 0.5 m m (Winder et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Johnson & Walton, ; Rennie et al . ), or after a period of exercise training (Rennie & Johnson, ; Beattie & Winder, , ; Adams & Koeslag, , ; Ohmori et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the decrease in malonyl-CoA during long-term, low-intensity exercise may occur by mechanisms other than phosphorylation of ACC. carnitine palmitoyltransferase-1; malonyl-coenzyme A; postexercise ketosis; 3-hydroxybutyrate POSTEXERCISE KETOSIS occurs after prolonged bouts of endurance exercise or after shorter bouts in fasted or carbohydrate-deficient states (2,3,7,13,14). In rats, the elevated 3-hydroxybutyrate levels seen during and after prolonged bouts of submaximal exercise are accompanied by a decline in liver malonyl-CoA (2,3,7).…”
mentioning
confidence: 99%